A comunicação matemática nos documentos curriculares da cidade de São Paulo no período de 2017 a 2019 - Oliveira, Fernando Araujo de (2021)
In view of the curricular elaboration or updating processes, triggered by the publication of the Base Nacional Comum Curricular - BNCC, the Municipal Education Secretariat of São Paulo published the “Currículo da Cidade: Matemática” (2017) that stood out for proposing several curricular innovations and, among them, the concern in addressing mathematical communication. The objective of this work is to investigate how mathematical communication proposals appear in the curriculum of the São Paulo city and in the related curriculum materials. For this, documentary research with a qualitative approach was developed, starting from the construction of theoretical foundation to characterize proposals with communicative potential and the bibliographic survey of Brazilian productions that reaffirm the relevance of the proposed study. Among the results we highlight the presence of communication in the development and learning objectives in all years of schooling, with more presence in the final years of elementary school. We observed that the objectives related to investigative practices have a higher occurrence of verbs that indicate communication, indicating the cognitive process to be mobilized with work. We also found that communicative practices related to language, such as orality, appear with balanced frequency, mainly in the complements of the objective, indicating a methodological action or degree of depth for the proposal. As for the objects of knowledge (content) to be worked on, we observe the presence of communication more frequently in the articulating axes “Extramathematical Connections”, “Games” and “Mathematical Processes” that concentrate almost the totality of proposals. Also, we observe how the proposals of the curricular material are presented, raising examples of how the communicative aspects are realized in sequences of activities to be developed together with the students.